The Role of Group Guidance with Psychodrama in Promoting Self-Adjustment: Does It Really Work for Adolescents? - Bila, Hanifa Salsa; Widyastuti, Dian Ari; Martaningsih, Sri Tutur; Agungbudiprabowo, Agungbudiprabowo; Mukti, Taquddin Abd (citeus, 2026)
This study aimed to examine the effectiveness of group guidance using psychodrama techniques in improving self-adjustment among students. The study employed a quantitative approach with an experimental research design, specifically a pretest–posttest control group design. The participants consisted of ten students, divided into an experimental group of five students and a control group of five students. The experimental group received group guidance with psychodrama techniques, while the control group received treatment as usual. The research participants were selected using a simple random sampling technique. Data were collected using a self-adjustment scale, which had been analyzed for validity and reliability using the Rasch model. The data were analyzed using an Independent Samples t-test. The results of the analysis using the independent sample t-test showed a significance value of 0,024 (<0,05). Based on the results of the data analysis, it can be concluded that group guidance with psychodrama techniques is effective in improving self-adjustment among senior high school students. Therefore, the findings of this study may serve as an alternative intervention for school counselors in enhancing students’ self-adjustment in the school setting.